THE RELATIONSHIP BETWEEN PEER FEEDBACK AND EFL STUDENTS’ SPEAKING ANXIETY IN DEBATE AND PUBLIC SPEAKING CLASS - Prasodjo, Bernadetha Ambarsari; Taloko, Johanes Leonardi (Yavana Bhasha : Journal of English Language Education, 2025)
This study examines the relationship between peer feedback and speaking anxiety among EFL students in debate and public speaking classes. Using a quantitative correlational design, data were collected from 82 participants using the Peer-Feedback Orientation Scale (PFOS) and the Public Speaking Class Anxiety Scale (PSCAS). Spearman correlation analysis revealed no significant relationship between peer feedback and speaking anxiety (r = -0.027; p = 0.808). These results indicate that while peer feedback improves critical thinking, engagement, and language performance, it does not directly reduce speaking anxiety. A holistic approach combining peer feedback with anxiety-reduction strategies is recommended. Future research should explore the long-term effects of such interventions in diverse cultural contexts.